Does current cefazolin dosing achieve adequate tissue and blood concentrations in obese women undergoing cesarean section?. (March 2017) - Kram, Jessica J.F.; Greer, Danielle M.; Cabrera, Omar; Burlage, Robert; Forgie, Marie M.; Siddiqui, Danish S.
Abstract: Background: Prophylactic administration of antibiotics preceding cesarean delivery is the most effective measure taken for preventing postpartum infection. While obese women are at greater risk for infection than non-obese women, evidence-based recommendations for modifying dosing in these women are limited. Objectives: The purpose of this study was to determine whether obese women undergoing cesarean delivery similarly reach adequate cefazolin concentrations within tissue and blood when weighing <120 kg and dosed 2 g versus weighing ≥120 kg and dosed 3 g. Study design: We prospectively studied women ≥18 years old with body mass index ≥30 kg/m 2 who underwent scheduled cesarean delivery with singleton pregnancy from August 2014 through March 2016. Women were dosed with 2 g and 3 g of cefazolin for body weights <120 kg and ≥120 kg, respectively. Samples of subcutaneous adipose tissue (following skin incision and before skin closure), myometrial tissue, fetal cord blood, and maternal blood were collected to assess whether cefazolin concentrations were adequate, i.e., at/above the minimum inhibitory concentration (MIC). Concentrations, based on inhibition zones for Streptococcus sanguinis, were calculated per gram of solid tissue and milliliter of blood. For all sample types, log-transformed concentrations were compared between dosage groups. Using a range of published MICs (1–8 μg/mL or μg/g), odds ratios, describing differential odds of falling below the MIC between dosage groups, were also computed. Results: Women who received 2 g (n = 65) versus 3 g (n = 19) of cefazolin did not significantly differ by maternal or gestational age, race/ethnicity, pre-operative hemoglobin, estimated blood loss, fluid administration, duration of surgery, or timing of sample collections relative to cefazolin administration ( P s > 0.05). Dosage groups also did not differ in cefazolin concentration (median [interquartile range]) within adipose tissue following skin incision (5.30 μg/g [3.00–9.60] vs. 6.35 μg/g [3.90–8.40]; P  = 0.551), adipose tissue before skin closure (4.45 μg/g [2.78–7.25] vs. 6.90 μg/g [2.60–10.6]; P  = 0.342), myometrial tissue (13.1 μg/g [8.60–19.6] vs. 15.7 μg/g [10.8–21.7]; P  = 0.116), or maternal blood (41.6 μg/mL [26.3–57.0] vs. 45.3 μg/mL [36.7–68.3]; P  = 0.143). However, cord blood concentrations differed significantly (19.5 μg/mL [13.7–28.5] vs. 27.9 μg/mL [15.8–39.4]; P  = 0.032), and, in 3 of 5 sample types, group concentrations differed at the dosing cut-point of 120 kg ( P s < 0.02). Within the range of MICs considered, differences in the odds of concentration inadequacy were not detected between dosage groups for any sample type. Across all patients, inadequate concentrations in one or more solid tissue types were observed in 1.19%, 17.9%, 59.5%, and 86.9% of patients, given the MICs of 1 μg/g, 2 μg/g, 4 μg/g and 8 μg/g, respectively. In adipose tissues, specifically, and both dosage groups, mean concentrations were significantly lower than the MIC of 8 μg/g ( P s < 0.03). Concentrations in one or both blood sample types were inadequate for only 8.33% of patients, given the 8-μg/mL MIC. Conclusions: Adequate cefazolin concentrations were achieved in blood for the majority of our patients. However, concentration adequacy was not achieved in solid tissue for a nearly equally large proportion of patients. Larger scale studies for determining modified protocols for dosing and applying MICs are warranted.